A homozygous R148W mutation in Semaphorin 7A causes progressive familial intrahepatic cholestasis - Qiong Pan; Gang Luo; Jiaquan Qu; Sheng Chen; Xiaoxun Zhang; Nan Zhao; Jingjing Ding; Hong Yang; Mingqiao Li; Ling Li; Ying Cheng; Xuan Li; et al. (EMBO Molecular Medicine)
Abstract Semaphorin 7A (SEMA7A) is a membrane‐bound protein that involves axon growth and other biological processes. SEMA7A mutations are associated with vertebral fracture and Kallmann syndrome. Here, we report a case with a mutation in SEMA7A that displays familial cholestasis. WGS reveals a SEMA7AR148W homozygous mutation in a female child with elevated levels of serum ALT, AST, and total bile acid (TBA) of unknown etiology. This patient also carried a SLC10A1S267F allele, but Slc10a1S267F homozygous mice exhibited normal liver function. Similar to the child, Sema7aR145W homozygous mice displayed elevated levels of serum ALT, AST, and TBA. Remarkably, liver histology and LC‐MS/MS analyses exhibited hepatocyte hydropic degeneration and increased liver bile acid (BA) levels in Sema7aR145W homozygous mice. Further mechanistic studies demonstrated that Sema7aR145W mutation reduced the expression of canalicular membrane BA transporters, bile salt export pump (Bsep), and multidrug resistance‐associated protein‐2 (Mrp2), causing intrahepatic cholestasis in mice. Administration with ursodeoxycholic acid and a dietary supplement glutathione improved liver function in the child. Therefore, Sema7aR145W homozygous mutation causes intrahepatic cholestasis by reducing hepatic Bsep and Mrp2 expression.